Preparative separation of nadolol racemates using reversed-phase liquid chromatography - Arafah, Rami (2016)
Nadolol is a nonselective beta-adrenergic receptor antagonist ( -blocker) pharmaceutical drug, widely used in the treatment of cardiovascular diseases, such as hypertension, ischemic heart disease (angina pectoris), congestive heart failure, and certain arrhythmias. Its chemical structure has three stereogenic centers which allows for eight possible stereoisomers. However, the two hydroxyl substituents on the cyclohexane ring are fixed in the cis-configuration, which precludes four stereoisomers; in fact, two pairs of enantiomers. Nadolol is presently marketed as an equal mixture of the four stereoisomers, designated as the diastereoisomers, There are still few published works concerning the separation of nadolol stereoisomers. Most of these works refer the resolution at analytical scale and few refer the separation at preparative scale using the simulated moving bed (SMB) technology [2-4]. This technology is generally based on the use of chiral adsorbents which must have enough recognition for all the chiral species.